The Nexus Between Social Media Activities, Destination Brand Awarness and Destination Brand Image - Hutahaeyan, Benny (Jurnal Ekonomi Efektif, 2025)
The aim of this study is to investigate the nexus between social media activities, destination brand awareness, and destination brand image in the destination of Kota Batu, East Java, Indonesia. The theoretical framework is grounded in customer-based brand equity, leveraging the role of social media activity in interacting with destination brand equity. This research employs a quantitative approach, distributing questionnaires to domestic tourists visiting the destination of Kota Batu. The determination of the sample size in this study utilizes the Slovin formula with the assistance of an online tool (www.qualtrics.com). This calculation also considers data from the Central Bureau of Statistics of Batu City regarding the total number of domestic tourists in 2022. Consequently, based on this calculation, 271 respondents were determined as the sample, particularly focusing on domestic tourists visiting tourist destinations in Batu City. The research findings suggest that destination brand awareness significantly mediates the relationship between interaction, trendiness, e-WOM, and destination brand image. A mediating variable implies that it can influence the relationship. The findings of this research indicate that the dimensions of social media activity have a positive and significant impact on destination brand awareness. Meanwhile, destination brand awareness positively and significantly influences destination image. Regarding the mediating role of destination brand awareness, it has a positive and significant effect.